Which is the best schedule of autologous blood storage for preoperative adolescent idiopathic scoliosis patients?. Issue 2 (December 2015) - Tamai, Koji; Terai, Hidetomi; Toyoda, Hiromitsu; Suzuki, Akinobu; Yasuda, Hiroyuki; Dozono, Shou; Nakamura, Hiroaki
Abstract Background It is critically important for AIS patients to avoid perioperative allogeneic blood transfusions. Toward this aim, many institutes use autologous blood storage to perform perioperative transfusions. However, there is no standard timeline for collecting blood for storage. Therefore, the objective of this prospective cohort study was to compare the outcome of two different schedules for collecting autologous blood before operation in adolescent idiopathic scoliosis (AIS) patients. Methods Inclusion criteria are AIS patients, younger than 20 years old, female, operated between 2009 and 2013 with posterior spinal fusion and instrumentation who had 1600 mL autologous blood collected before operation. A total of 61 patients were participated in this study. They were randomly divided into 2 groups based on the storage interval. Weekly group (1W-G) consisted of 30 patients with a total of 1600mL blood collected weekly beginning 4 weeks before the operation. Biweekly group (2W-G) consisted of 31 patients with a total of 1600 mL blood collected biweekly beginning 8 weeks before the operation. The instrumented levels, total bleeding, complications during blood transfusion, and hematological examinations (RBC, Hb, Hct, MCH, MCV, MCHC) were evaluated. A hematological examination was performed before blood collection, before the operation, and on postoperative days 1, 3, and 7. Vasovagal reflex (VVR) was evaluated as complications during blood drawing. Result Mean age, height, and weight did not differ significantly between the 2 groups. There were no significant differences in instrumented levels, bleeding during operation, after operation, and collected blood during operation. With the autologous blood, allogeneic blood transfusion was completely avoided. VVR was more frequent in the biweekly group significantly (1W-G 4.2% vs 2W-G 15.3%). In terms of hematological examination, all values showed no significant differences between two groups in the pre-drawing and the pre-operation stage. However, the postoperative Hb and Hct values were higher in the weekly group. Also, MCV and MCHC showed the same behavior with higher values in the weekly group. Conclusion A weekly schedule of autologous blood storage is better than a biweekly storage schedule.